Clinical Practice Guideline: Sudden Hearing Loss (Update). (1st August 2019) - Chandrasekhar, Sujana S.; Tsai Do, Betty S.; Schwartz, Seth R.; Bontempo, Laura J.; Faucett, Erynne A.; Finestone, Sandra A.; Hollingsworth, Deena B.; Kelley, David M.; Kmucha, Steven T.; Moonis, Gul; Poling, Gayla L.; Roberts, J. Kirk; et al.
Abstract : Objective: Sudden hearing loss is a frightening symptom that often prompts an urgent or emergent visit to a health care provider. It is frequently but not universally accompanied by tinnitus and/or vertigo. Sudden sensorineural hearing loss affects 5 to 27 per 100, 000 people annually, with about 66, 000 new cases per year in the United States. This guideline update provides evidence‐based recommendations for the diagnosis, management, and follow‐up of patients who present with sudden hearing loss. It focuses on sudden sensorineural hearing loss in adult patients aged ≥18 years and primarily on those with idiopathic sudden sensorineural hearing loss. Prompt recognition and management of sudden sensorineural hearing loss may improve hearing recovery and patient quality of life. The guideline update is intended for all clinicians who diagnose or manage adult patients who present with sudden hearing loss. Purpose: The purpose of this guideline update is to provide clinicians with evidence‐based recommendations in evaluating patients with sudden hearing loss and sudden sensorineural hearing loss, with particular emphasis on managing idiopathic sudden sensorineural hearing loss. The guideline update group recognized that patients enter the health care system with sudden hearing loss as a nonspecific primary complaint. Therefore, the initial recommendations of this guideline update address distinguishing sensorineural hearing loss from conductive hearing loss at the time of presentation with hearing loss. They also clarify the need to identify rare, nonidiopathic sudden sensorineural hearing loss to help separate those patients from those with idiopathic sudden sensorineural hearing loss, who are the target population for the therapeutic interventions that make up the bulk of the guideline update. By focusing on opportunities for quality improvement, this guideline should improve diagnostic accuracy, facilitate prompt intervention, decrease variations in management, reduce unnecessary tests and imaging procedures, and improve hearing and rehabilitative outcomes for affected patients. Methods: Consistent with the American Academy of Otolaryngology–Head and Neck Surgery Foundation's "Clinical Practice Guideline Development Manual, Third Edition" (Rosenfeld et al. Otolaryngol Head Neck Surg . 2013;148[1]:S1‐S55), the guideline update group was convened with representation from the disciplines of otolaryngology–head and neck surgery, otology, neurotology, family medicine, audiology, emergency medicine, neurology, radiology, advanced practice nursing, and consumer advocacy. A systematic review of the literature was performed, and the prior clinical practice guideline on sudden hearing loss was reviewed in detail. Key Action Statements (KASs) were updated with new literature, and evidence profiles were brought up to the current standard. Research needs identified in the original clinical practice guideline and data addressing them were reviewed. Current research needs were identified and delineated. Results: The guideline update group made strong recommendations for the following: (KAS 1) Clinicians should distinguish sensorineural hearing loss from conductive hearing loss when a patient first presents with sudden hearing loss. (KAS 7) Clinicians should educate patients with sudden sensorineural hearing loss about the natural history of the condition, the benefits and risks of medical interventions, and the limitations of existing evidence regarding efficacy. (KAS 13) Clinicians should counsel patients with sudden sensorineural hearing loss who have residual hearing loss and/or tinnitus about the possible benefits of audiologic rehabilitation and other supportive measures. These strong recommendations were modified from the initial clinical practice guideline for clarity and timing of intervention. The guideline update group made strong recommendations against the following: (KAS 3) Clinicians should not order routine computed tomography of the head in the initial evaluation of a patient with presumptive sudden sensorineural hearing loss. (KAS 5) Clinicians should not obtain routine laboratory tests in patients with sudden sensorineural hearing loss. (KAS 11) Clinicians should not routinely prescribe antivirals, thrombolytics, vasodilators, or vasoactive substances to patients with sudden sensorineural hearing loss. The guideline update group made recommendations for the following: (KAS 2) Clinicians should assess patients with presumptive sudden sensorineural hearing loss through history and physical examination for bilateral sudden hearing loss, recurrent episodes of sudden hearing loss, and/or focal neurologic findings. (KAS 4) In patients with sudden hearing loss, clinicians should obtain, or refer to a clinician who can obtain, audiometry as soon as possible (within 14 days of symptom onset) to confirm the diagnosis of sudden sensorineural hearing loss. (KAS 6) Clinicians should evaluate patients with sudden sensorineural hearing loss for retrocochlear pathology by obtaining magnetic resonance imaging or auditory brainstem response. (KAS 10) Clinicians should offer, or refer to a clinician who can offer, intratympanic steroid therapy when patients have incomplete recovery from sudden sensorineural hearing loss 2 to 6 weeks after onset of symptoms. (KAS 12) Clinicians should obtain follow‐up audiometric evaluation for patients with sudden sensorineural hearing loss at the conclusion of treatment and within 6 months of completion of treatment. These recommendations were clarified in terms of timing of intervention and audiometry and method of retrocochlear workup. The guideline update group offered the following KASs as options : (KAS 8) Clinicians may offer corticosteroids as initial therapy to patients with sudden sensorineural hearing loss within 2 weeks of symptom onset. (KAS 9a) Clinicians may offer, or refer to a clinician who can offer, hyperbaric oxygen therapy combined with steroid therapy within 2 weeks of onset of sudden sensorineural hearing loss. (KAS 9b) Clinicians may offer, or refer to a clinician who can offer, hyperbaric oxygen therapy combined with steroid therapy as salvage therapy within 1 month of onset of sudden sensorineural hearing loss. Differences from Prior Guideline: Incorporation of new evidence profiles to include quality improvement opportunities, confidence in the evidence, and differences of opinion Included 10 clinical practice guidelines, 29 new systematic reviews, and 36 new randomized controlled trials Highlights the urgency of evaluation and initiation of treatment, if treatment is offered, by emphasizing the time from symptom occurrence Clarification of terminology by changing potentially unclear statements; use of the term sudden sensorineural hearing loss to mean idiopathic sudden sensorineural hearing loss to emphasize that >90% of sudden sensorineural hearing loss is idiopathic sudden sensorineural hearing loss and to avoid confusion in nomenclature for the reader Changes to the KASs from the original guideline: KAS 1—When a patient first presents with sudden hearing loss, conductive hearing loss should be distinguished from sensorineural. KAS 2—The utility of history and physical examination when assessing for modifying factors is emphasized. KAS 3—The word "routine" is added to clarify that this statement addresses nontargeted head computerized tomography scan that is often ordered in the emergency room setting for patients presenting with sudden hearing loss. It does not refer to targeted scans, such as temporal bone computerized tomography scan, to assess for temporal bone pathology. KAS 4—The importance of audiometric confirmation of hearing status as soon as possible and within 14 days of symptom onset is emphasized. KAS 5—New studies were added to confirm the lack of benefit of nontargeted laboratory testing in sudden sensorineural hearing loss. KAS 6—Audiometric follow‐up is excluded as a reasonable workup for retrocochlear pathology. Magnetic resonance imaging, computerized tomography scan if magnetic resonance imaging cannot be done, and, secondarily, auditory brainstem response evaluation are the modalities recommended. A time frame for such testing is not specified, nor is it specified which clinician should be ordering this workup; however, it is implied that it would be the general or subspecialty otolaryngologist. KAS 7—The importance of shared decision making is highlighted, and salient points are emphasized. KAS 8—The option for corticosteroid intervention within 2 weeks of symptom onset is emphasized. KAS 9—Changed to KAS 9A and 9B. Hyperbaric oxygen therapy remains an option but only when combined with steroid therapy for either initial treatment (9A) or salvage therapy (9B). The timing of initial therapy is within 2 weeks of onset, and that of salvage therapy is within 1 month of onset of sudden sensorineural hearing loss. KAS 10—Intratympanic steroid therapy for salvage is recommended within 2 to 6 weeks following onset of sudden sensorineural hearing loss. The time to treatment is defined and emphasized. KAS 11—Antioxidants were removed from the list of interventions that the clinical practice guideline recommends against using. KAS 12—Follow‐up audiometry at conclusion of treatment and also within 6 months posttreatment is added. KAS 13—This statement on audiologic rehabilitation includes patients who have residual hearing loss and/or tinnitus who may benefit from treatment. Addition of an algorithm outlining KASs Enhanced emphasis on patient education and shared decision making with tools provided to assist in same